2015
DOI: 10.1016/j.ccell.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Stimulates Tumor Growth via EphB4

Abstract: SUMMARY While recombinant human erythropoietin (rhEpo) has been widely used to treat anemia in cancer patients, concerns about its adverse effects on patient survival have emerged. A lack of correlation between expression of the canonical EpoR and rhEpo’s effects on cancer cells prompted us to consider the existence of an alternative Epo receptor. Here, we identified EphB4 as an Epo receptor that triggers downstream signaling via STAT3 and promotes rhEpo induced tumor growth and progression. In human ovarian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 47 publications
(49 reference statements)
2
71
1
Order By: Relevance
“…Another study by Pradeep et al . reported that EphB4 receptor promotes tumor growth and progression via stimulation of STAT3 signaling26. We noticed reduced expression of phosphorylated and total STAT3 in PDX tumors following sEphB4-HSA treatment with radiation.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Another study by Pradeep et al . reported that EphB4 receptor promotes tumor growth and progression via stimulation of STAT3 signaling26. We noticed reduced expression of phosphorylated and total STAT3 in PDX tumors following sEphB4-HSA treatment with radiation.…”
Section: Discussionmentioning
confidence: 49%
“…Enhanced apoptosis is one of the key anti-tumor responses mediated by EphB4 targeting and radiation325262728. In caspase-3/7 assay, we observed a significant increase in apoptosis (~28%) in Fadu cells transfected with EphB4-siRNA and 4 Gy dose of radiation compared to radiation alone at 96 h (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Human Breast Cancer cell line MDA-MB-231 and human epithelial ovarian cancer cell lines SKOV3ip1, HeyA8, A2274, A2780, OVCAR5, OVCAR8, RMG2, and IGROV1 were maintained as described previously (Pradeep et al, 2015). Human immortalized umbilical endothelial cells (RF24) and human dermal microvascular endothelial cells were grown in MEM medium with supplements (sodium pyruvate, non-essential amino acids, MEM vitamins, and glutamine; Life Technologies, Grand Island, NY).…”
Section: Matrials and Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously reported (Pradeep et al, 2015, Haemmerle et al, 2017). Cell lysate of RF24 cells were treated with human recombinant EGFL6 protein or anti-EGFL6 antibodies and checked for activation of PI3kinase and AKT signaling by using anti-human EGFL6, PI3kinase, and AKT antibodies followed by secondary antibodies conjugated with horseradish peroxidase.…”
Section: Matrials and Methodsmentioning
confidence: 99%